PEMBAHARUAN HUKUM PIDANA MENURUT RKUHP TAHUN 2018 TERHADAP PELAKU PENYALAHGUNAAN NARKOTIKA DENGAN SISTEM REHABILITASI - Aditia Arief Firmanto (Universitas Bandar Lampung (UBL), 2019)
Criminal Law Reform is an effort to form laws and regulations that are in accordancewith the conditions of the community, whose main goal is to achieve the ideals of Indonesia,namely not only regulating citizens through laws, but also creating peace and prosperitythrough state institutions that has the authority to make related regulations. The 2018Criminal Code (RKUHP) Draft has the goal of renewing sanctions imposed on perpetratorsof narcotics abuse with a rehabilitation system. Narcotics according to Law No. 35 of 2009concerning Narcotics is a substance or drug derived from plants both synthesis and semisynthesisthatcancauseadecreaseorchangeofconsciousness,lossofpainandcancausedependence.Regulations regarding sanctions for the penal system as outlined in the draftRKUHP 2018 are motivated by a number of basic ideas or principles, one of which is theidea of using a doubble track (between criminal and action) so that in the concept there areprovisions that are not in the Criminal Code currently in force, but one alternative criminalis the possibility of combining types of sanctions (criminal and action). In addition point 3 ofthe Supreme Court Circular No. 4 of 2010 regulates that rehabilitation in narcotic crimes iscarried out with integrated assessment, which consists of a team of doctors, namely doctorsand psychologists, a legal team, namely from the police, National Narcotics Agency (BNN),Prosecutors' Office and kemenkumham after issuing a recommendation that someone is aconcurrent user as a dealer or purely as an addict. Barriers to criminal law reformaccording to the RUHUHP 2018 against narcotics abusers with the rehabilitation systeminclude the RKUHP and Rubber Article that makes Narcotics Users sent to Prisons andnarcotics stigma is not a health problem